Case Report: Response of cutaneous lupus lesions in SLE to interferon receptor blockade parallels reduction of interferon score in blood - Günther, Claudia; Wolf, Christine; Fennen, Louisa; Rösing, Sarah; Beissert, Stefan; Aringer, Martin; Lee-Kirsch, Min Ae (Frontiers in Immunology, 2023)
Cutaneous lupus erythematosus (CLE), the main manifestation of systemic lupus erythematosus (SLE), is driven by type I interferons (IFNs) and often only partially responds to conventional therapies. Treatment of seven SLE patients with the monoclonal antibody anifrolumab induced fast and sustained remission of previously refractory CLE lesions, beginning within the first weeks of treatment. Decline in CLASI-A score was paralleled by a reduction in IFN score determined by mRNA expression of seven IFN-stimulated genes (ISGs) in blood. These data suggest that a subset of ISGs could be a valuable biomarker in CLE.